If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying u + 4 = 11 + -2(2u + -9) Reorder the terms: 4 + u = 11 + -2(2u + -9) Reorder the terms: 4 + u = 11 + -2(-9 + 2u) 4 + u = 11 + (-9 * -2 + 2u * -2) 4 + u = 11 + (18 + -4u) Combine like terms: 11 + 18 = 29 4 + u = 29 + -4u Solving 4 + u = 29 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. 4 + u + 4u = 29 + -4u + 4u Combine like terms: u + 4u = 5u 4 + 5u = 29 + -4u + 4u Combine like terms: -4u + 4u = 0 4 + 5u = 29 + 0 4 + 5u = 29 Add '-4' to each side of the equation. 4 + -4 + 5u = 29 + -4 Combine like terms: 4 + -4 = 0 0 + 5u = 29 + -4 5u = 29 + -4 Combine like terms: 29 + -4 = 25 5u = 25 Divide each side by '5'. u = 5 Simplifying u = 5
| 2(3b+2)-7=9 | | 13-4/2x=37 | | x^2+13x+65=0 | | 4=2(x+3) | | 4(n-2)= | | 0=8z-(3-2) | | 3r+22= | | x+10/3=4 | | X-7(x+4)=68 | | 2+2x-3=2x-4+3x-1 | | -6n-2n=15 | | 0.3t+0.18(5000-t)=0.21(5000) | | x(8x+19)=3x^2-14x+56 | | y-55=9x-45 | | 4x+16=80 | | -5y+12=4(2y+3) | | -0.312-2.4x=0.9(2.5x+1.1) | | 2n+n+-3=9 | | 6x-2=x-7 | | (3/5(25/9))-(2/3) | | (2x-1)(4+5x)=0 | | 3/2a=75 | | 3x-21=2x-21 | | x+(1/4)x=(7/8) | | 3(2x-1)-2=13 | | 302-2a=210 | | 3/4m-5-1/2m | | 2-1/2=x | | m+4-4m+3= | | (x+2.1)-(0.1x+3)=11 | | x-10403=116 | | 5b=3.55 |